Interactive Effects of Light Quality and Temperature on Arabidopsis Growth and Immunity. (7th April 2020) - Liu, Xiaoying; Xue, Chunmei; Kong, Le; Li, Ruining; Xu, Zhigang; Hua, Jian
Abstract: We report here the interactive effects of three light qualities (white, red and blue) and three growth temperatures (16C, 22C and 28C) on rosette growth, hypocotyl elongation and disease resistance in Arabidopsis thaliana. While an increase in temperature promotes hypocotyl elongation irrespective of light quality, the effects of temperature on rosette growth and disease resistance are dependent on light quality. Maximum rosette growth rate under white, red and blue light are observed at 28C, 16C and 22C, respectively. The highest disease resistance is observed at 16C under all three light conditions, but the highest susceptibility is observed at 28C for white light and 22C for red and blue light. Interestingly, rosette growth is inhibited by phytochrome B (PHYB) under blue light at 28C and by cryptochromes (CRYs) under red light at 16C. In addition, disease resistance is inhibited by PHYB under blue light and promoted by CRYs under red light. Therefore, this study reveals a complex interaction between light and temperature in modulating rosette growth and disease resistance as well as the contribution of PHYB and CRY to disease resistance.